Answer: x = 9 y = 5
Step-by-step explanation: I like to use elimination for problems like these. Start by multiplying everything in the second equation (x - 3y = -6) by 4. Your equation should then look like this: 4x - 12y = -24
Now add the two equations as if they were two numbers:
-4x + 9y = 9
4x - 12y = -24
Your x's will cancel out and 9y + -12y = -3y and 9 + -24 = -15. This will make your new equation look like:
-3y = -15
Divide both sides by -3 and you get that y = 5
Substitute 5 in for y for any of the original given equations and solve:
-4x + 9y = 9
-4x + 9(5) = 9
-4x + 45 = 9
-4x = -36
x = 9